Australian population trends and disparities in cholinesterase inhibitor use, 2003 to 2010 - Zilkens, Renate; Duke, Janine; Horner, Barbara; Semmens, James; Bruce, D. (Elsevier, 2014)
Background: The Australian Pharmaceutical Benefits Scheme (PBS) first subsidized cholinesteraseinhibitors (CEIs) for Alzheimer’s disease in 2001, introducing a novel therapy fora previously untreatable common condition. This study aims to determine Australian rates ofCEI use and to assess equality of access to treatment based on socioeconomic status andgeographic remoteness.Methods: Pharmaceutical claims records were used to identify all Australians prescribed CEIsbetween January 2003 and December 2010. Age-standardized and sex-adjusted index prescriptionrates were derived using the total Australian population as the denominator to examine temporaltrends and the impacts of socioeconomic and geographic disadvantage on CEI index prescriptionrates.Results: Index prescription rates peaked in 2004 at 92.5 per 100,000 person-years, declining tobetween 70.2 and 73.5 for years 2006 to 2010. Rates were highest in the 85- to 89-year age groupand 2.6-fold higher in the least socioeconomic disadvantaged population when compared with themost disadvantaged population. In major cities in Australia, index prescription rates were 1.4 to1.7 times greater compared with remote areas.Conclusions: Increasing geographic remoteness and socioeconomic disadvantage are associatedwith lower CEI index prescription rates, indicating inequities in the management of Alzheimer’sdisease in Australia.